Analisis Naskah Monolog “Apakah Kita Sudah Merdeka” Karya Putu Wijaya (Jurnal Insan Pendidikan dan Sosial Humaniora, 2023)
This research analyzes two monologue scripts by renowned writer Putu Wijaya, titled "Aeng" and "Are We Already Free?" using an objective approach and qualitative research method. Literature is considered as a mirror of society that reflects human life, while drama and theater are seen as forms of portraying human life in a performance. Monologue, as a type of drama performed by a single actor, is the main focus of this study. Through the analysis of themes, plot, setting, and messages conveyed in the monologue scripts, this research aims to enrich understanding of literature, the genre of drama and theater, as well as the techniques and strategies employed in monologues. The implications of this research include a deeper understanding of the portrayal of life in literature, expanded knowledge of Putu Wijaya's literary works, comprehension of monologues as a performance form, a more objective perspective in understanding and appreciating literary works, and a more profound and contextual understanding of themes, plot, setting, and messages within the monologue scripts. This study is expected to contribute to the enrichment of literary and dramatic understanding and provide deeper insights into monologues as a form of performance.